Free marketing : 101 low and no-cost ways to grow your business, online and off - Cockrum, Jim, 1969- (Hoboken, N.J. : Wiley, 2011)
'There's never been a better time to be a marketer or entrepreneur than right now. Thanks to the Internet, there is a world of free and very inexpensive ways to get the word out. Free Marketing takes us through all these online tips and tricks and explains how best to promote our businesses. However, the book goes beyond the obvious, it covers so much more than the online tricks you'd expect. Whilst half the book looks at online opportunities for free promotion, the other half is full of ingenious and innovative ways to market for free offline. And these are tried and tested techniques; the author uses them for his own business and brings in millions with almost no marketing budget.The book includes 100 free marketing ideas, including: Use eBay to auction your services - author made $30,000 in one auction doing this Create a'squeeze page', the most powerful one page website you'll ever build Use YouTube videos to grow sales Turn your top 20 customers into your sales force Find a common enemy that your customers hate Join forces with the competition'--
Includes index.
Keywords: Marketing; Branding (Marketing); Internet marketing; Corporate image; BUSINESS & ECONOMICS / Marketing / General